Antecedent SMEs Performance: The Interaction Effect of External Integration - Sari, Ni Komang Santi Yullia; Srinita, Ni Wayan; Sapta, I Ketut Setia; Utami, Ni Made Satya; Rustiarini, Ni Wayan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Competence and entrepreneurial orientation are key factors in maintaining the resilience of SME businesses. Specifically this study has the following objectives; (1) to identify the effect of entrepreneurial orientation (EO) on the performance of SME companies, (2) to identify the effect of entrepreneurial competence (EC) on the performance of SME companies (3) to identify the effect of EO on the performance of SME companies with external integration moderation variables (ExIn), (4) to identify the effect of EC on the performance of SME companies with external integration moderation variables (ExIn). The population and sample of this study are small and medium enterprises (SMEs) in several districts/cities in the province of Bali with respondents owners/leaders of SMEs several 150 people. Data analysis using SEM approach and processing with the help of Smart PLS 3.2.2. The results showed; the first hypothesis that entrepreneurial orientation (EO) has a positive effect on the performance of SME companies (FP). Based on the test results obtained the first hypothesis is accepted. The results of the second hypothesis test that entrepreneurial competence (EC) has a positive effect on the performance of SME companies (FP). The second hypothesis was rejected. Hasip tested the third hypothesis that external integration can moderate (strengthen) the influence of entrepreneurial competence (EC) on the performance of SMEs. The third hypothesis (H3) was rejected.